The supplementation of Fermented Feed (Indegofera Sp and Eurycoma longifolia) Leaves on Arabic Chicken Semen - Mustaqim Mustaqim; Zulkifli zulkifli; Cut Rauzatul Jannah; Salsabila (Warmadewa University Press, 2021)
This study aims to determine the effect of fermented feed in the form of Indegofera Sp and Eurycoma Longifolia (El) leaves on the quality of Arabian chicken semen. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments consisted of P.1 : Commercial Feed, P.2 : 80% Indegofera sp + 20% Eurycoma longifolia (El) leaves, P.3: 70% Indegofera sp leaves + 30% Eurycoma longifolia (El) leaves, P.4 : 60% Indegofera sp + 40% Eurycoma longifolia (El) leaves. Semen collection was carried out on day 30 after feeding. The semen quality were observed and analyzed using one-way analysis of variance (ANOVA) followed by Duncan's test. The results showed that the combination of two fermented feed (Indegofera Sp and Eurycoma Longifolia) leaves had a significant effect (P<0.05) on the quality of arab chicken spermatozoa. The fermented feed is able to improve the quality of Arabic chicken semen.